Automated guidance and learning prototype for people with visual disabilities - Arizaga-Usnayo, Luis; Cabrera-Rodriguez, Mathias; Cruz-Torres, Angel; Montoya-Magallanes, Alvaro; Lazo-Barreda, Dely; Aparicio-Maldonado, Edmundo; Villegas Medina, Jaime (LACCEI, 2025)
Visual impairment significantly limits a person’s ability to interact with their environment and poses additional challenges in early learning, particularly for children. This paper presents the design and development of a wearable assistive prototype aimed at enhancing spatial awareness and learning capabilities for individuals with visual disabilities. The device integrates object recognition, text reading, and GPS-based navigation using artificial intelligence and embedded vision systems. A survey conducted among individuals familiar with visual impairment revealed high interest and acceptance of the proposed solution. Findings suggest a strong demand for accessible tools that foster autonomy and improve learning experiences. The implementation of such a prototype in regions like Arequipa may have substantial impact on social inclusion and educational access for visually impaired populations.